Implementing University Social Responsibility in the Caribbean: Perspectives of Internal Stakeholders - Gomez, Lina M. (2018)
University Social Responsibility (USR) is the ethical and transparent management of the administrative, educational, cognitive and social processes carried out by a higher education institution. More and more universities are practicing USR not only in Latin America but also in the United States and Europe, in order to reduce the negative impacts their daily operations can have on different stakeholders and on a macro level on society, the economy, and the environment. However, despite existing knowledge in the implementation of USR in Latin America and the Caribbean, there are few empirical studies that analyze the positions of diverse internal stakeholders regarding USR practices mainly in the Caribbean. Therefore, this study analyzes the perspectives of the internal stakeholders in social responsibility initiatives and processes at a private university in Puerto Rico. A total of 533 participants (356 students, 99 administrative staff, and 78 faculty members) were interviewed and were given a questionnaire, which evaluated the following areas: responsible campus, professional and citizenship education, social knowledge management, and social participation. Overall, the internal stakeholders’ perceptions were consistent among the three groups. It can be observed that the various internal stakeholders are aware of what it means—in theory, and in practice—, to be a socially-responsible university, although they also recognize opportunities for improvement and future challenges regarding USR. The results of this study contribute to the literature, to the application of conceptual models—mainly from the perspectives of internal stakeholders—and to the importance of evaluating USR practices.